AL-QUR’AN MENURUT PANDANGAN ORIENTALIS (Studi Analisis ‘Teori Pengaruh’ dalam Pemikiran Orientalis) - Muzayyin, M. (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
ewline"> This article tries to discuss the discourse proposed by modern westernscholarship regarding to the study of polemicies about Qur’anic studies,that it is an inflence theory developed in nineteen century. The scholarsused historical criticism as one of biblical method. Shortly, by using thishistorical criticism, they attempted to trace back the inflence of Jewish orChristian ideas toward the Qur’a>n. As a result this paper fids that whenMuhammad came up with some Qur’anic doctrines, such as the history ofprophethood, as well the terminology in the Qur’an; were not simply allegedor adopted from both of Jewish and Christian. This polemecies issue werepopularized mainly by Abraham Geiger, then followed by Teodor Noldeke,William Muir, and John Wansbrough that will be on this article.